Kant on the Universality of Moral Principles: An Analysis - Barman, Sanjit (Asian Journal of Philosophy and Religion, 2025)
This article examines the foundation of moral principles in Kant’s philosophy. It argues that within Kant’s ethical framework, moral principles are not derived from empirical observation or contingent circumstances but from the a priori universality and necessity of reason. Central to this system is the categorical imperative—Kant’s supreme principle of morality—which requires that moral actions must be willed as if they could become universal law. Accordingly, I argued that in Kant’s moral philosophy, true freedom constitutes not merely the absence of external constraints but the positive capacity to act according to reason. This conception of rational autonomy underpins Kant’s principle of equality. As every individual possessing this same capacity is inherently equal in moral worth. Similarly, respect for persons fundamentally entails respect for the moral law itself since recognising human dignity involves acknowledging each individual’s capacity for rational self-legislation. The exploration of the universality of moral principles in Kant’s moral philosophy, on the one hand, provides a robust and enduring framework for understanding freedom, equality and justice as interdependent elements of a rational moral system; on the other hand, it demonstrates how this universality remains critically relevant for addresing contemporary moral dilemmas.